2022
DOI: 10.4103/ijdr.ijdr_357_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sealing Ability of MTA and Retroplast as Root End Filling Materials Evaluated under a Stereomicroscope Using Rhodamine B Dye

Abstract: Aim: The aim of the study was to compare the sealing ability of Mineral Trioxide Aggregate (MTA) and Retroplast as root end filling materials using the Rhodamine B dye penetration method in vitro. Methodology: Forty freshly extracted human single-rooted teeth were randomly divided into two groups of 20 teeth each, and standard root-end cavities were prepared in all teeth. The cavities were filled with MTA and Retroplast in groups 1 and 2, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Nepal et al [ 32 ] compared the apical microleakage of glass ionomer, MTA, and Biodentine by the dye penetration test using 2% methylene blue, and showed that after 72 h, MTA and Biodentine had significantly lower leakage than glass ionomer, but the difference between MTA and Biodentine was not significant. In another study, Kararia et al [ 33 ] evaluated the seal ability of MTA and Retroplast by the dye penetration test using 1% Rhodamine B. They reported that after 1 week, leakage was noted in 95% of all specimens in both groups, with no significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Nepal et al [ 32 ] compared the apical microleakage of glass ionomer, MTA, and Biodentine by the dye penetration test using 2% methylene blue, and showed that after 72 h, MTA and Biodentine had significantly lower leakage than glass ionomer, but the difference between MTA and Biodentine was not significant. In another study, Kararia et al [ 33 ] evaluated the seal ability of MTA and Retroplast by the dye penetration test using 1% Rhodamine B. They reported that after 1 week, leakage was noted in 95% of all specimens in both groups, with no significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome can be attributed to the outstanding sealing ability of MTA, which effectively prevents the microleakage of bacteria. In a study conducted by Kararia et al [ 27 ], a comparison was made between the sealing ability of MTA and retroplast. The researchers concluded that MTA demonstrated superior performance when compared with retroplast.…”
Section: Discussionmentioning
confidence: 99%